The Talaandigs' Ulaging Pagkabihag Ta Nalandangan and the Agpangan-Gantangan-Timbangan Cultural Framework - Savior, Hobart (2023)
This is a qualitative, descriptive, and ethnographic study of the Ulaging Pagkabiha Nalandangan and the Agpangan - Gantangan Timbangan cultural framework of the Talaandigs of Songco, Lantapan, Bukidnon. Part of a larger proto-Manobo Ulahingan te Ulaging of the Talaandigs recounts the exploits of Agy and his men against invaden and enemies. The episode Pagkabihag Ta Nalandangan, which is the focus of this study, tells the struggles of Agyu and the other Ulagingens to reclaim their territory called Nalandangan it was captured by their enemy, Padsilong Ha Kabatlaw. The paper explores how the Ulager expresses the Talaandig culture and illustrates their collective and societal identity, including theit Batasan, the sacred customary code or law, and their aspiration as a people and nation attain self-determination, survival, and development. The Talaandigs value their Ulaging articulates their struggles as a community to protect and defend their ancestral domain and territory, the integrity of their culture and identity, their traditional leadership and governance their intellectual property, and their full sovereignty. The Ulaging mirrors in fact the l life experiences of the Talaandigs and the way that it does so can be seen in the Agpangan

-Gantangan - Timbangan cultural framework at work in the narrative. The Ulaging is the Agpangan or the basis and constitutionality of the Talaandig existence, while the principle and measure of fairness, Gantangan, and the principle of balance to achieve harmony, equalis and justice, called Timbangan, are illustrated in the life of Agyu, whose leadership qualities and authority as a hero the Talaandigs strive to emulate. The Ulaging guides the Talaandigs in handling and pursuing the spiritual, educational, social, political, economic, and territorial aspects of their lives.
Keywords: Ulaging (Epic)